2006
DOI: 10.1016/j.neuroscience.2005.11.031
|View full text |Cite
|
Sign up to set email alerts
|

Lithium increases bcl-2 expression in chick cochlear nucleus and protects against deafferentation-induced cell death

Abstract: Approximately 20-30% of neurons in the avian cochlear nucleus (nucleus magnocellularis) die following deafferentation (i.e. deafness produced by cochlea removal) and the remaining neurons show a decrease in soma size. Cell death is generally accepted to be a highly regulated process involving various pro-survival and pro-death molecules. One treatment that has been shown to modify the expression of these molecules is chronic administration of lithium. The present experiments examined whether lithium treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 42 publications
1
25
0
Order By: Relevance
“…Only 0.8% of the deafferented NM neurons would be considered labeled in brains from lithium-treated subjects. The 0.8% of labeled cells may seem somewhat low since Bush and Hyson (2006) did report some cell death in the lithium-treated subjects. One possible explanation of this discrepancy is that the effects of lithium in the present experiment were evaluated on the same day as cochlea removal.…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…Only 0.8% of the deafferented NM neurons would be considered labeled in brains from lithium-treated subjects. The 0.8% of labeled cells may seem somewhat low since Bush and Hyson (2006) did report some cell death in the lithium-treated subjects. One possible explanation of this discrepancy is that the effects of lithium in the present experiment were evaluated on the same day as cochlea removal.…”
Section: Discussionmentioning
confidence: 84%
“…Previous work (Bush and Hyson, 2006) showed that chronic lithium administration protected NM neurons from deafferentation-induced cell death, but did not prevent the deafferentation-induced reduction in soma size. The present sets of experiments examined different events that occur in the cell death cascade in deafferented NM neurons to determine which of these events are influenced by chronic lithium administration.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations